2020
DOI: 10.1007/s12182-020-00482-6
|View full text |Cite
|
Sign up to set email alerts
|

Cause analysis and solutions of water blocking damage in cracked/non-cracked tight sandstone gas reservoirs

Abstract: After hydraulic fracturing treatment, a reduction in permeability caused by the invasion of fracturing fluids is an inevitable problem, which is called water blocking damage. Therefore, it is important to mitigate and eliminate water blocking damage to improve the flow capacities of formation fluids and flowback rates of the fracturing fluid. However, the steady-state core flow method cannot quickly and accurately evaluate the effects of chemical agents in enhancing the fluid flow capacities in tight reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It can be seen that the reservoir formation porosity and pore throat radius varied greatly at different depths, but that the matrix was relatively tight in general, and that the pore size distribution contributing to the permeability was mainly 1.9–0.16 μm. Therefore, potential water blocking damage might exist [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the reservoir formation porosity and pore throat radius varied greatly at different depths, but that the matrix was relatively tight in general, and that the pore size distribution contributing to the permeability was mainly 1.9–0.16 μm. Therefore, potential water blocking damage might exist [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, based on the study of reservoir geological characteristics, Dongyu et al [14] used laboratory experiments to determine the reservoir damage mechanism during water injection and believed that strong water sensitivity and high water injection intensity were the main damages in the development process. In the same year, Wang and Zhou [15] used electron microscope scanning technology to study the difference in water plugging damage between uncracked cores and cracked cores and evaluated the improvement effect of the new nanoemulsion on microclogging and liquid flow capacity. In 2021, Zhu et al [16] reviewed the application research progress of NMR technology in the role of polymer gels, showing that it has broad application prospects in evaluating the performance of gel and monitoring the improvement effect of gel.…”
Section: Introductionmentioning
confidence: 99%
“…However, the flow behavior in a tight gas reservoir is complex. It has been found that such a reservoir has a threshold pressure gradient [9,10]; the permeability in a tight gas reservoir may change with pressure and exhibits a stress-sensitive effect during the production process [11,12]; the proppant embedment issues in the hydraulic fractures of a tight reservoir may affect the gas production [13]; the temperature and pressure may affect the imbibition recovery for tight or shale gas reservoir [14]; the tight gas production may be seriously reduced by water blockage [15][16][17]; the dispersed distribution of kerogen within matrices may affect the production evaluation [18]; sulfur precipitation and reservoir pressure-sensitive effects may affect the permeability, porosity and formation pressure [19]; the micro-scale flow mechanism, such as Knudsen diffusion, slippage effect, and adsorption, can be difficult to describe quantitatively [20,21]. All these complexities associated with tight gas reservoirs make it difficult to build an accurate mathematical model to predict gas flow in tight gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%